Sleep Complaints as Risk Factor for Suicidal Behavior in Severely Depressed Children and Adolescents. (18th August 2016) - Lopes, Maria‐Cecilia; Boronat, Alexandre C.; Wang, Yuan‐Pang; Fu‐I, Lee
Summary: Objectives: To investigate the association between sleep complaints and suicidal behaviors among severely depressed children and adolescents. Methods: The sample was 214 youths (56.1% males, mean age 12.5 years) with diagnosis of DSM‐IV major depressive disorder consecutively recruited from a university‐based outpatient clinic specialized in mood disorders. The structured interview for children and adolescents was applied to participants. The Children's Depression Rating Scale—revised version—scored the severity of depression, and the Children's Global Assessment Scale assessed the global functioning. Subgroups of patients were compared for psychopathological association by means of logistic regression, in accordance with presence and absence of sleep complaints and suicidality. Results: The frequency of sleep complaints and suicidal behaviors was, respectively, 66.4% and 52.3%, and both symptoms were observed in 37.9% of patients. Initial insomnia was the most frequent manifestation (58%), followed by night awakening (36%), daytime sleepiness (31%), and early awakening (29.9%). Significant association between sleep disturbance and suicidal behavior was found (odds ratio range of 2.3–10.8). Conclusion: Sleep disturbances are potential warning manifestations of suicidal behaviors in depressed youth. Possibly, the severity of the active affective episode likely underlies in both sleep complaints and suicidal behaviors among depressed underage patients.